THE IMPACT OF AUDITOR ROTATION ON PUBLIC SECTOR AUDIT QUALITY AND ACCOUNTABILITY - Adriyana Adevia Nuryadin; Amiruddin Amiruddin; Asri Usman (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This study aims to analyze the impact of auditor rotation on audit quality and accountability in the public sector through a literature review approach. Auditor rotation is a policy designed to maintain auditor independence and minimize the risk of excessive closeness between the auditor and the audited entity. The research method used is a literature review, examining various scientific sources such as journals, books, and research reports relevant to the topics of auditor rotation, audit quality, and public accountability. The results of the study indicate that auditor rotation has a complex impact on audit quality. On the one hand, auditor rotation can enhance independence and objectivity, potentially improving audit quality and financial reporting transparency. However, on the other hand, auditor rotation can also pose challenges in the form of a loss of auditor-specific knowledge of the audited entity, which in the short term can reduce the efficiency and effectiveness of the audit process. Therefore, auditor rotation needs to be balanced with a sound transition strategy to optimize its benefits to audit quality and accountability.